Undifferentiated Connective Tissue Disease in Pregnancy: A Topic Yet to be Explored - Serena, Caterina; Clemenza, Sara; Simeone, Serena; Zullino, Sara; Ottanelli, Serena; Rambaldi, Marianna Pina; Vannuccini, Silvia; Petraglia, Felice; Mecacci, Federico (Frontiers in Pharmacology, 2022)
Undifferentiated connective tissue disease (UCTD) is characterized by signs and symptoms suggestive of a connective tissue disease (CTD), but not fulfilling criteria for a specific CTD. Although UCTD is probably the most common rheumatic disease diagnosed in pregnant women, data about disease course during pregnancy and perinatal outcomes are very limited. Compared to other CTDs, UCTD seems to have milder clinical manifestations in pregnancy. Its natural history is related to disease activity at conception. In fact, if the disease is in a state of remission or minimal activity at conception, pregnancy outcomes are generally good. On the contrary, patients who become pregnant in a moment of high disease activity and/or who have multiple antibodies positivity show an increased risk of disease flares, evolution to a definite CTD and obstetric complications, such as fetal growth restriction, preeclampsia and preterm birth. Therefore, a preconception assessment is essential in women with UCTD to evaluate maternal and fetal risks, to initiate interventions to optimize disease activity, and to adjust medications to those that are least harmful to the fetus. The aim of the present study was to review the available literature about pregnancy course, maternal and fetal outcomes and therapeutic approaches of pregnant women with UCTD.